EVALUASI SEKOLAH DASAR TERDAMPAK GEMPA BUMI DI KECAMATAN CUGENANG KABUPATEN CIANJUR - Dedy Swandry Banurea; Adi Wibowo (JURNAL GEOGRAFI, 2023)
Earthquake events are disasters that cannot be predicted and have the possibility of recurring. The earthquake that hit Cianjur Regency on November 22 2022 provided lessons in dealing with and evaluating affected areas and sectors so that going forward it would be able to reduce victims and damage. Cugenang District is one of the sub-districts affected by the earthquake, plus a fault zone or Cugenang Fault has been identified. One of the sectors affected is the education sector, especially elementary schools in their teaching and learning activities. This study aims to identify the distribution pattern of elementary schools as a trigger factor for evaluating locations with an earthquake risk index level. As for the evaluation, the Nearest Neighbor Analysis (NNA) method and overlay analysis were used so that a random distribution pattern was obtained in Elementary Schools that followed settlements, and Elementary Schools with high levels of damage were obtained in locations with high earthquake indexes so that they were used as basis for consideration of relocation. Keywords :GIS; NNA; Earthquake; Elementary School; Cugenang